Basic principals of the tiltrotors flight control system architecture and algorithms - M. I. Myasnikov; I. R. Ilyin (Научный вестник МГТУ ГА)
This study describes the main structure and algorithm development principles of flight control systems for tiltrotor aircraft using the example of rotary-wing aircraft V-22 Osprey and AW609. A brief overview of convertiplane performance is provided. Typical conversion corridors are given using the example of convertiplanes XV-15 and AW609. The principles of V-22 and AW609 tiltrotor control system development are described. The design objectives of the automatic control system of the convertible aircraft are listed. The structure of the control system is discussed in detail. The development principles of control laws for Normal and Direct operational modes are described. Hydraulic power supply systems for control actuators are considered. Examples of the main control system architecture with triple redundancy for V-22 and AW609 convertiplanes are given. Main characteristics of tiltrotor control laws are given. Main functions of tiltrotor automatic control systems are described. Methods for ensuring high reliability of the flight control system, ways to reduce crew workload in order to ensure compliance with the regulatory requirements of V-22 tiltrotor handling qualities are considered. Features of AW609 tiltrotor flight control system development, requirements for control laws which make it possible to reduce crew workload, improve handling qualities and increase the reliability of the control system are considered. As an example, the automatic flight control system (autopilot) algorithm synthesis of a light tiltrotor for all flight modes (helicopter, aircraft and conversion) is given. The possibility of using a relatively simple algorithms and structure of automatic control system during the flight and conversion between the helicopter – aircraft – helicopter modes is shown.